Composite material for efficiently curing incineration fly ash heavy metal and preparation method and application thereof
By combining biochar and zeolite and combining silicate groups and organic groups, a composite material that efficiently cures the heavy metals of incinerated fly ash is formed, solving the problem of difficult to coordinate the treatment of multiple heavy metals in the prior art, and achieving the effect of efficiently reducing the toxicity of heavy metals in the leaching of incinerated fly ash is achieved.
Patent Information
- Application Number
- CN202411552149.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-25
AI Technical Summary
The prior art is difficult to efficiently coordinate the disposal of a variety of heavy metals in incinerated fly ash, and there is an antagonistic effect between the heavy metals, resulting in the difficulty of reducing the toxicity of heavy metals in incinerated fly ash.
By combining biochar and zeolites and sequentially modifying them with silicate groups and organic groups, composite materials with high specific surface area and loaded silicate groups and organic groups are formed, and these groups are used to form complexes or precipitates with heavy metals in the incinerated fly ash, thereby reducing the effectiveness and mobility of heavy metals.
The leaching toxicity of lead, cadmium, zinc and chromium in incinerated fly ash is significantly reduced, efficient curing and stabilization is achieved, and when the added amount is 1% of the mass of fly ash, the leaching content of heavy metals can be lower than the limits specified in the "Standard for Landfill Pollution Control of Domestic Waste".
Smart Images

Figure CN119499608A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of heavy metal treatment of incineration fly ash, in particular to a composite material for efficiently solidifying heavy metals in incineration fly ash, and a preparation method and application thereof. Background Art
[0002] In recent years, the incineration fly ash produced during the incineration of domestic waste contains a variety of high-concentration heavy metals and is a hazardous waste. It is necessary to reduce the effectiveness, mobility and migration of heavy metals in the incineration fly ash so that the toxicity concentration of heavy metals leaching meets the prescribed limit requirements before it can be landfilled in the municipal solid waste landfill. How to safely and efficiently dispose of incineration fly ash is a difficulty faced by ecological and environmental protection. At present, the solidification and stabilization of incineration fly ash followed by landfill disposal has become a hot spot in my country's environmental protection field and market at this stage. The solidification and stabilization materials are mainly divided into organic and inorganic materials. Studies have shown that in the process of solidifying and stabilizing heavy metals in incineration fly ash, biochar and zeolite have significant advantages due to their unique structure.
[0003] Among them, biochar has a large specific surface area and rich functional groups such as -OH, -COOH, C=O on the surface, which can complex or precipitate heavy metals such as lead, cadmium, zinc and chromium in incineration fly ash, thereby reducing the mobility and effectiveness of heavy metals in incineration fly ash. Zeolite is a crystalline hydrated aluminum silicate mineral, mainly composed of SiO2, Al2O3, alkali metals and H2O. Its basic skeleton is composed of multiple silicon oxygen tetrahedrons (SiO4) and aluminum oxygen tetrahedrons (AlO4). The large amount of Si-OH on the outer edge of its tetrahedral structure can react with heavy metals. At the same time, due to the three-dimensional network structure composed of its Si and Al atoms through oxygen bridge bonds and the surrounding four oxygen atoms, it can absorb heavy metals in the crystal frame structure, further solidifying and stabilizing heavy metals. Biochar and zeolite have good adsorption and ion exchange properties due to their special spatial structure. After the two are compounded and modified, the inner diameter of the pores increases, which greatly improves the adsorption performance, improves the solidification and stabilization effect, and significantly reduces the toxicity of heavy metal leaching from incineration fly ash.
[0004] For example, Chinese patent publication No. CN116407800A discloses a method for removing heavy metals from waste incineration fly ash by EDTA ball milling reaction. The patent uses ethylenediaminetetraacetic acid (EDTA) to mix with incineration fly ash and water for preparation, and then obtains slurry through ball milling reaction, and finally obtains fly ash toxic slag by heap leaching. The heavy metal leaching concentration of Pb, Zn, Cd, Ni, Cu, Cr, Hg and other heavy metals in the fly ash slag is determined according to the leaching procedure of "Solid Waste Leaching Toxicity Leaching Method Acetic Acid Buffer Solution Method" (HJ / T 300-2007), which meets the landfill disposal requirements of the national standard "Pollution Control Standard for Municipal Waste Landfill" (GB 16889-2008). This patent uses EDTA as an ingredient to mix with incineration fly ash, which can effectively reduce the leaching toxicity of various heavy metals such as Pb, Zn, Cd, etc. in the incineration fly ash. However, the process requires ball mill mechanical processing, which is costly, and the slurry obtained by the ball milling reaction will produce leachate when stacked, which requires further disposal, causing secondary environmental pollution. It does not strictly follow the "three-transformation" principles of solid waste pollution prevention and control.
[0005] The article "Study on the Effect of EDTA-modified Zeolite on the Adsorption of Ammonia Nitrogen in Groundwater Contaminated by Landfill Leachate" published by Sun Shuhai et al. mentioned that zeolite was used as raw material and modified with disodium ethylenediaminetetraacetic acid solution to study the adsorption effect of modified zeolite on ammonia nitrogen pollutants in groundwater contaminated by landfill leachate. It was found that the optimal removal rate of ammonia nitrogen was in the pH range of 6 to 8, and the optimal adsorption time was 120 minutes. Therefore, considering that zeolite has a unique structure and EDTA is a common complex, it has a certain important reference role in the removal of heavy metal ions by EDTA-modified zeolite.
[0006] At present, biochar and zeolite have been widely studied in the prevention and control of solid waste pollution, and some of the research has been implemented and promoted in engineering projects. EDTA, as an important organic chelating agent, has been lacking in research, and the combined modification of the three in the treatment of multiple heavy metals in the fly ash of municipal solid waste incineration has been less studied and lacks application. When existing biochar and zeolite are used to treat multiple heavy metals in the fly ash of incineration, they cannot achieve efficient coordinated treatment of multiple heavy metals, and the heavy metals show antagonism.
[0007] Therefore, in view of the characteristics of incineration fly ash, it is urgent to study a composite material that can efficiently solidify heavy metals in incineration fly ash to facilitate the harmless disposal of hazardous waste incineration fly ash. Summary of the invention
[0008] In order to solve the above technical problems, the present invention provides a composite material for efficiently solidifying heavy metals in incineration fly ash, and a preparation method and application thereof.
[0009] To achieve the above object, the present invention is implemented according to the following technical solutions:
[0010] One of the purposes of the present invention is to provide a method for preparing a composite material for efficiently solidifying heavy metals in incineration fly ash, comprising the following steps:
[0011] S1. Take biochar and zeolite, dry them separately and grind them, mix the ground biochar and zeolite in a mass ratio of 1:(0.5-2), mix and stir evenly to obtain a biochar / zeolite composite material;
[0012] S2, adding the biochar / zeolite composite material to a metal silicate solution for the first modification at room temperature, and after the reaction is completed, performing solid-liquid separation, and drying the solid phase to obtain a silicate-modified biochar / zeolite composite material;
[0013] S3. Adding the silicate-modified biochar / zeolite composite material to an ethylenediaminetetraacetic acid metal salt solution for a second modification at room temperature, and after the reaction is completed, performing solid-liquid separation and solid phase drying to obtain a silicate-organic group composite modified biochar / zeolite composite material.
[0014] Furthermore, in step S2, 20-50 g of biochar / zeolite composite material is added to each liter of metal silicate solution, and the reaction is stirred at room temperature for 1-4 hours; the metal silicate solution is a 0.2-1.1 mol / L sodium silicate solution or potassium silicate solution or a mixed solution of sodium silicate and potassium silicate.
[0015] Furthermore, in step S3, 10-80 g of silicate-modified biochar / zeolite composite material is added to each liter of ethylenediaminetetraacetic acid metal salt solution, and the reaction is stirred at room temperature for 1-4 hours; the ethylenediaminetetraacetic acid metal salt solution is a 0.10-1.30 mol / L disodium ethylenediaminetetraacetic acid solution or a dipotassium ethylenediaminetetraacetic acid solution or a mixed solution of disodium ethylenediaminetetraacetic acid and dipotassium ethylenediaminetetraacetic acid.
[0016] Furthermore, in the step S1, the biochar and zeolite are dried at 35°C-40°C, ground and sieved through a 20-30 mesh sieve.
[0017] Furthermore, in the steps S2 and S3, the solid phase drying is to dry the collected solid phase at 25°C-45°C.
[0018] A second object of the present invention is to provide a composite material for efficiently solidifying heavy metals in incineration fly ash prepared by the method according to any one of claims 1 to 5.
[0019] A third object of the present invention is to provide a composite material for efficiently solidifying heavy metals in incineration fly ash as claimed in claim 6 for use in solidifying heavy metals in incineration fly ash.
[0020] Furthermore, the heavy metals are lead, cadmium, zinc and chromium.
[0021] Specifically, the composite material for efficiently solidifying heavy metals in incineration fly ash is used as a solidifying and stabilizing material, and is added at 1.0%-3.0% of the mass of the incineration fly ash and stirred evenly; and water is added at 30%-50% of the mass of the incineration fly ash and mixed and stirred for 10-30 minutes. After being fully mixed, it is placed in a natural state for 2 to 7 days.
[0022] Preferably, the composite material for efficiently solidifying heavy metals in incineration fly ash is added in an amount of 1.0% by mass of the incineration fly ash.
[0023] The principle of the present invention is as follows: the present invention sequentially modifies the biochar / zeolite composite material with silicate groups and organic groups for the following purposes: first, the composite modification of biochar and zeolite increases the specific surface area of the composite material, improves the void structure and increases the void ratio, improves the adsorption performance of the composite material itself, and is conducive to forming chelate precipitates or complexes with heavy metals; second, the composite material increases the silicate groups (such as -SiO3 2- ) and organic groups (such as -C 10 H 14 N2O8 2- ), these groups can form metal coordination complexes with heavy metals such as lead, cadmium, zinc and chromium through complexation and coprecipitation. The carboxyl group in EDTA provides an oxygen atom with a lone pair of electrons, which overlap with the empty orbital of heavy metal ions to form a coordination bond. EDTA forms a complex with heavy metal ions through coordination bonds, which greatly enhances the curing performance of the composite modified material. The synergistic effect of the two further reduces the effectiveness of heavy metals in incineration fly ash, thereby significantly reducing the leaching toxicity of heavy metals in incineration fly ash.
[0024] Compared with the prior art, the composite material for efficiently solidifying heavy metals in incineration fly ash provided by the present invention is that the biochar / zeolite composite material is modified by silicate groups and organic groups in sequence, the specific surface area and porosity of the biochar and the zeolite itself are significantly improved, and at the same time, a large number of silicate groups and organic groups are promoted to be loaded on the surface, and these groups can form metal coordination complexes with lead, cadmium, zinc and chromium in the fly ash heavy metals through complexation, coprecipitation and the like, and the two can play a synergistic role, thereby enhancing the adsorption performance of the biochar and zeolite composite for lead, cadmium, zinc and chromium, and can simultaneously and efficiently solidify and stabilize the lead, cadmium, zinc and chromium in the fly ash, and when the addition amount is 1% of the fly ash mass, the solidification and stabilization treatment can be performed once to make the leaching content of lead, cadmium, zinc and chromium in the incineration fly ash lower than the limit value specified in the "Standard for Pollution Control of Municipal Waste Landfill" (GB16889-2008), the application prospect is good, and the preparation process is simple, normal temperature and pressure, environmentally friendly, and free of secondary pollution, and it has great promotion value. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1This is a process flow chart for preparing the composite modified biochar / zeolite composite material in Example 1.
[0026] Figure 2 This is the solidification and stabilization effect of the composite modified biochar / zeolite composite material in Example 4 on heavy metals (lead, cadmium, zinc and chromium) in incineration fly ash.
[0027] Figure 3 This is the solidification and stabilization effect of the composite modified biochar / zeolite composite material in Example 5 on heavy metals (lead, cadmium, zinc and chromium) in incineration fly ash. DETAILED DESCRIPTION
[0028] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. The specific embodiments described herein are only used to explain the present invention and are not used to limit the invention.
[0029] Example 1
[0030] (1) Compounding pretreatment: drying the biochar and zeolite at 40°C and grinding them through a 20-sieve sieve; compounding the dried and sieved biochar and zeolite in a ratio of 1:1, mixing and stirring evenly to obtain a biochar / zeolite compound material;
[0031] (2) Silicate-based modification: The biochar / zeolite composite material prepared in step (1) was added to a sodium silicate solution with a concentration of 0.5 mol / L for the first modification. 30 g of the biochar / zeolite composite material was added to each liter of the sodium silicate solution. The mixture was stirred at room temperature for 2 h, and the solid-liquid separation was performed. After the solid phase was dried at 45° C., a silicate-based modified biochar / zeolite composite material was obtained.
[0032] (3) Organic group composite modification: The silicate-modified biochar / zeolite composite material prepared in step (2) was added with 0.60 mol / L disodium ethylenediaminetetraacetic acid (C 10 H 14 N2O8Na2 was used for the second modification, and each liter of disodium ethylenediaminetetraacetate (C 10 H 14 N2O8Na2) was added with 20 g of silicate-modified biochar / zeolite composite material, and the mixture was stirred at room temperature for 3 h. After solid-liquid separation and solid phase drying at 50°C, the mixture was passed through a 40-mesh sieve to obtain a silicate-organic group composite modified biochar / zeolite composite material, which was recorded as sample 1.
[0033] The surface morphology and surface element content of sample 1 were analyzed by scanning electron microscopy-energy spectrum (SEM-EDS). The surface was loaded with 11% silicon, 48% carbon, 9% nitrogen and 15% sodium by mass fraction, of which silicon was loaded in the form of silicate groups, and carbon and nitrogen were loaded in the form of organic groups. The pH was measured by a pH meter and was 7.6. The specific surface area was measured by a specific surface area detector and was 45.91 m 2 / g, the particle size measured by a particle size analyzer is 0.3mm, and the pore volume measured by a pore volume meter is 0.09cm 3 / g.
[0034] Example 2
[0035] (1) Compounding pretreatment: drying the biochar and zeolite at 35°C and grinding them through a 20-sieve sieve; compounding the dried and sieved biochar and zeolite in a ratio of 1:0.5, mixing and stirring evenly to obtain a biochar / zeolite compound material;
[0036] (2) Silicate modification: The biochar / zeolite composite material prepared in step (1) was added to a potassium silicate solution with a concentration of 0.8 mol / L for the first modification. 40 g of the biochar / zeolite composite material was added to each liter of potassium silicate solution. The mixture was stirred at room temperature for 3 h, and the solid-liquid separation was performed. After the solid phase was dried at 45° C., a silicate-modified biochar / zeolite composite material was obtained.
[0037] (3) Organic group composite modification: The silicate-modified biochar / zeolite composite material prepared in step (2) was added with 0.60 mol / L dipotassium ethylenediaminetetraacetate (C 10 H 14 N2O8K2) solution for the second modification, each liter of ethylenediaminetetraacetic acid dipotassium (C 10 H 14 30 g of silicate-modified biochar / zeolite composite material was added to the N2O8K2) solution, and the reaction was stirred at room temperature for 4 h. After solid-liquid separation and solid phase drying at 45°C, the composite material was passed through a 40-mesh sieve to obtain a silicate-organic group composite modified biochar / zeolite composite material, which was recorded as sample 2.
[0038] The surface morphology and surface element content of sample 2 were analyzed by scanning electron microscopy-energy spectrum (SEM-EDS). The surface was loaded with 12% silicon, 36% carbon, 7% nitrogen, 12% sodium and 8% potassium by mass fraction, of which silicon was loaded in the form of silicate groups, and carbon and nitrogen were loaded in the form of organic groups. The pH was measured by a pH meter and was 8.1. The specific surface area was measured by a specific surface area detector and was 51.82 m 2 / g, the particle size measured by a particle size analyzer is 0.3mm, and the pore volume measured by a pore volume meter is 0.08cm3 / g.
[0039] Example 3
[0040] (1) Compound pretreatment: drying the biochar and zeolite at 40°C and grinding them through a 30-sieve sieve; compounding the dried and sieved biochar and zeolite in a ratio of 1:2, mixing and stirring evenly to obtain a biochar / zeolite compound material;
[0041] (2) Silicate-based modification: The biochar / zeolite composite material obtained in step (1) is added to a sodium silicate / potassium silicate mixed solution with a concentration of 1.0 mol / L for the first modification. 30 g of the biochar / zeolite composite material is added to each liter of the sodium silicate / potassium silicate mixed solution. The mixture is stirred at room temperature for 2 h, and the solid-liquid separation is performed. After the solid phase is dried at 45° C., a silicate-based modified biochar / zeolite composite material is obtained.
[0042] (3) Organic group composite modification: The silicate-modified biochar / zeolite composite material prepared in step (1) was added with 0.60 mol / L dipotassium ethylenediaminetetraacetate (C 10 H 14 N2O8K2) EDTA disodium (C 10 H 14 N2O8Na2) mixed solution for the second modification, each liter of ethylenediaminetetraacetic acid dipotassium (C 10 H 14 N2O8K2) EDTA disodium (C 10 H 14 40 g of silicate-modified biochar / zeolite composite material was added to the mixed solution of N2O8Na2, and the reaction was stirred at room temperature for 3 h. After solid-liquid separation and solid phase drying at 45°C, the composite material was passed through a 60-mesh sieve to obtain a silicate-organic group composite modified biochar / zeolite composite material, which was recorded as sample 3.
[0043] The surface morphology and surface element content of sample 3 were analyzed by scanning electron microscopy-energy spectrum (SEM-EDS). The surface was loaded with 15% silicon, 36% carbon, 7% nitrogen, 13% sodium and 12% potassium by mass fraction, of which silicon was loaded in the form of silicate groups, and carbon and nitrogen were loaded in the form of organic groups. The pH was measured by a pH meter and was 7.8. The specific surface area was measured by a specific surface area detector and was 63.91 m 2 / g, the particle size was measured by a particle size analyzer to be 0.4 mm, and the pore volume was measured by a pore volume meter to be 0.10 cm 3 / g.
[0044] Application Example 1
[0045] In this example, sample 2 prepared in Example 2 is used as a heavy metal solidification and stabilization material to evaluate its effect on the solidification and stabilization of heavy metals in incineration fly ash, wherein the incineration fly ash is taken from a municipal solid waste incineration power plant in a certain area. According to the leaching method of "Solid Waste Leaching Toxicity Leaching Method-Acetic Acid Buffer Solution Method" (HJ / T300-2007), the leaching contents of heavy metals lead, cadmium, zinc and chromium in the incineration fly ash are respectively measured, and the results are 1.80 mg / L, 1.17 mg / L, 182 mg / L and 5.82 mg / L, respectively. The leaching contents of heavy metals lead, cadmium, zinc and chromium in the incineration fly ash are all higher than the "Standard for Pollution Control of Municipal Solid Waste Landfill" (GB 16889-2008). After the incineration fly ash is naturally air-dried, it is ground through a 60-mesh sieve for standby use;
[0046] The specific steps include:
[0047] Five groups of incineration fly ash were taken respectively, each with a dry weight of 1000g. One group was blank group (CK) without adding solidification and stabilization materials, one group was added with 1% unmodified biochar material as control group (BC), one group was added with 1% unmodified zeolite material as control group (FS), one group was added with 1% unmodified biochar and zeolite material as control group (BF), one group was added with 1% biochar / zeolite composite modified material as experimental group (BF-SE), and 200g water was added to each group for mixing and stirring for 20 minutes. After sufficient mixing, it was placed in a natural state for curing for 2 days.
[0048] After curing, the ash was dried, ground and passed through a 20-mesh sieve. The heavy metal leaching content of the fly ash was determined according to the leaching procedure of "Solid Waste Leaching Toxicity Leaching Method-Acetic Acid Buffer Solution Method" (HJ / T300-2007). The results are shown in Table 1. Compared with the limit values specified in the "Landfill Pollution Control Standard for Municipal Waste" (GB 16889-2008), the results are shown in Table 1. Figure 2 shown.
[0049] Table 1 The solidification and stabilization effect of biochar / zeolite composite modified materials on heavy metals (lead, cadmium, zinc and chromium) in incineration fly ash
[0050]
[0051] As can be seen from Table 1, compared with the control group, the silicate-organic group composite modified biochar / zeolite material used in the experimental group significantly reduced the leaching content of lead, cadmium, zinc and chromium in the incineration fly ash, indicating that the biochar / zeolite composite modified material provided by the present invention can simultaneously solidify and stabilize lead, cadmium, zinc and chromium in the incineration fly ash, and the leaching effects of heavy metal lead, cadmium, zinc and chromium after solidification and stabilization of the composite modified material are 1.59 times, 1.32 times, 1.89 times and 1.34 times that of the control group (BF), respectively, which are significantly different from the control group (P<0.05).
[0052] Compared with the control groups BC, FS, and BF, although the leaching content of heavy metals lead, cadmium, zinc, and chromium in the incineration fly ash is reduced after treatment, it is still excessive. The biochar / zeolite composite modified material provided by the present invention can make the leaching content of heavy metals lead, cadmium, zinc, and chromium in the incineration fly ash lower than the limit value specified in GB 16889-2008 after one treatment, indicating that the stabilization material provided by the present invention has a significantly better solidification and stabilization ability for lead, cadmium, zinc, and chromium in the incineration fly ash. Moreover, after adding 1% of the biochar / zeolite composite modified material provided by the present invention and stabilizing it once, the leaching content of heavy metals lead, cadmium, zinc, and chromium in the fly ash meets the limit value requirements specified in the "Landfill Pollution Control Standard for Domestic Waste" (GB 16889-2008), and it can be directly landfilled after stabilization treatment.
[0053] Application Example 2
[0054] In this example, sample 3 prepared in Example 3 was used as a heavy metal solidification and stabilization material to evaluate its effect on the solidification and stabilization of heavy metals in incineration fly ash, wherein the incineration fly ash was taken from a municipal solid waste incineration power plant in a certain area. According to the leaching method of "Solid Waste Leaching Toxicity Leaching Method-Acetic Acid Buffer Solution Method" (HJ / T300-2007), the leaching contents of heavy metals lead, cadmium and zinc in the incineration fly ash were respectively measured, and the results were 1.80 mg / L, 1.17 mg / L, 182 mg / L and 5.82 mg / L, respectively. The leaching contents of heavy metals lead, cadmium, zinc and chromium in the incineration fly ash were all higher than the "Standard for Pollution Control of Municipal Solid Waste Landfill" (GB 16889-2008). After the incineration fly ash was naturally air-dried, it was ground through a 40-mesh sieve for standby use;
[0055] The specific steps include:
[0056] Four groups of incineration fly ash were taken respectively, each with a dry weight of 500g. One group was blank group (CK) without adding solidification and stabilization materials, one group was added with 1% unmodified biochar material as control group (BC), one group was added with 1% unmodified zeolite material as control group (FS), one group was added with 1% unmodified biochar and zeolite material as control group (BF), one group was added with 1% biochar / zeolite composite modified material as experimental group (BF-SE), 100g water was added to each group and mixed and stirred for 30 minutes. After sufficient mixing, it was placed in a natural state for curing for 7 days.
[0057] After curing, the ash was dried, ground and passed through a 20-mesh sieve. The heavy metal leaching content of the fly ash was determined according to the leaching procedure of "Solid Waste Leaching Toxicity Leaching Method-Acetic Acid Buffer Solution Method" (HJ / T300-2007). The results are shown in Table 2. Compared with the limit values specified in the "Landfill Pollution Control Standard for Municipal Waste" (GB 16889-2008), the results are shown in Table 2. Figure 3 shown.
[0058] Table 2 The solidification and stabilization effect of biochar / zeolite composite modified materials on heavy metals (lead, cadmium, zinc and chromium) in incineration fly ash
[0059]
[0060] As shown in Table 2, compared with the control group (BF), the biochar / zeolite composite modified material used in the experimental group significantly reduced the leaching content of lead, cadmium, zinc and chromium in the incineration fly ash. The composite modified zeolite reduced the leaching content of lead, cadmium and zinc by 82.61%, 86.21%, 53.15% and 21.69%, respectively. Compared with the control group, there was a significant difference (P<0.05). The leaching content of heavy metals lead, cadmium, zinc and chromium in the incineration fly ash after solidification and stabilization by the biochar / zeolite composite modified material was 1.52 times, 1.33 times, 2.06 times and 1.24 times that of the control group (BF), respectively. This shows that when the addition amount of the experimental group BF-SE was 1%, the curing time was extended to 7 days, and the heavy metal leaching concentration of the incineration fly ash was lower than the standard limit, while the heavy metal leaching concentration of the incineration fly ash in the control groups BC, FS and BF was still excessive and higher than the landfill standard limit.
[0061] In summary, the composite material for efficiently solidifying heavy metals in incineration fly ash prepared by the present invention can simultaneously promote the loading of a large number of silicate groups and organic groups on its surface, and these groups can form metal coordination complexes with lead, cadmium, zinc and chromium in fly ash heavy metals through complexation, co-precipitation and the like, and the two can play a synergistic role, thereby enhancing the adsorption performance of the biochar and zeolite composite pair for lead, cadmium, zinc and chromium, and can simultaneously and efficiently solidify and stabilize the lead, cadmium, zinc and chromium in fly ash.
[0062] The technical solution of the present invention is not limited to the above-mentioned specific embodiments. All technical variations made according to the technical solution of the present invention fall within the protection scope of the present invention.
Claims
1. A method for preparing a composite material for efficiently solidifying heavy metals in incineration fly ash, characterized in that: The following steps are involved: S1. Take biochar and zeolite, dry them separately and grind them, mix the ground biochar and zeolite in a mass ratio of 1:(0.5-2), mix and stir evenly to obtain a biochar / zeolite composite material; S2, adding the biochar / zeolite composite material to a metal silicate solution for the first modification at room temperature, and after the reaction is completed, performing solid-liquid separation, and drying the solid phase to obtain a silicate-modified biochar / zeolite composite material; S3. Adding the silicate-modified biochar / zeolite composite material to an ethylenediaminetetraacetic acid metal salt solution for a second modification at room temperature, and after the reaction is completed, performing solid-liquid separation and solid phase drying to obtain a silicate-organic group composite modified biochar / zeolite composite material.
2. The method for preparing a composite material for efficiently solidifying heavy metals in incineration fly ash according to claim 1, characterized in that: In the step S2, 20-50 g of biochar / zeolite composite material is added to each liter of metal silicate solution, and the mixture is stirred and reacted at room temperature for 1-4 hours; the metal silicate solution is a 0.2-1.1 mol / L sodium silicate solution or potassium silicate solution or a sodium silicate potassium silicate mixed solution.
3. The method for preparing a composite material for efficiently solidifying heavy metals in incineration fly ash according to claim 1, characterized in that: In the step S3, 10-80 g of silicate-modified biochar / zeolite composite material is added to each liter of ethylenediaminetetraacetic acid metal salt solution, and the mixture is stirred and reacted at room temperature for 1-4 hours; the ethylenediaminetetraacetic acid metal salt solution is a 0.10-1.30 mol / L disodium ethylenediaminetetraacetic acid solution or a dipotassium ethylenediaminetetraacetic acid solution or a mixed solution of disodium ethylenediaminetetraacetic acid and dipotassium ethylenediaminetetraacetic acid.
4. The method for preparing a composite material for efficiently solidifying heavy metals in incineration fly ash according to claim 1, characterized in that: In the step S1, the biochar and zeolite are dried at 35° C.-40° C., ground and sieved through a 20-30 mesh sieve.
5. The method for preparing a composite material for efficiently solidifying heavy metals in incineration fly ash according to claim 1, characterized in that: In the steps S2 and S3, the solid phase drying is to dry the collected solid phase at 25°C-45°C.
6. A composite material for efficiently solidifying heavy metals in incineration fly ash prepared by the method according to any one of claims 1 to 5.
7. Use of the composite material for efficiently solidifying heavy metals in incineration fly ash as claimed in claim 6 in solidifying heavy metals in incineration fly ash.
8. The use according to claim 7, characterized in that: The heavy metals are lead, cadmium, zinc and chromium.
9. The use according to claim 7, characterized in that: The composite material for efficiently solidifying heavy metals in incineration fly ash as claimed in claim 6 is used as a solidifying and stabilizing material, and is added at 1.0%-3.0% of the mass of the incineration fly ash and stirred evenly; and water is added at 30%-50% of the mass of the incineration fly ash and mixed and stirred for 10-30 minutes. After being fully mixed, it is placed in a natural state for 2 to 7 days.
10. The use according to claim 9, characterized in that: The composite material for efficiently solidifying heavy metals in incineration fly ash is added according to 1.0% of the mass of the incineration fly ash.
Citation Information
Patent Citations
Method for removing heavy metal in waste incineration fly ash through EDTA ball-milling reaction
CN116407800A